(untitled) (Purbanchal University Health Journal, 2024)
Introduction: Hypertension is one of the silent killers in the 21st century and is one of the largest global public health concerns. An estimated 1.28 billion people aged 79 years worldwide have hypertension, with the two-thirds residing in low and middle-income country. In Nepal, about one in every four people has hypertension, and less than 5% have it under control. Objective: The objective of the study was to assess the knowledge on hypertension among adults in a community. Method: A descriptive cross-sectional design was used to assess the knowledge on hypertension among adults. A convenience sampling technique was used to select the respondents. A structured interview schedule was used to collect the data among 423 respondents. Descriptive and inferential analysis i.e. chi-square test was used to find the association between dependent and independent variables. Result: The finding of the study revealed that less than one third (27.9 %) of respondents were aged between 31 to 40 years. More than half (52.7%) were male, less than one third (28.6%) of respondents were dependent on service. Similarly, more than half (53.4%) of the respondents had no family history of hypertension less than half (42.6%) of respondents were Brahmin/ Chhetri, 44.4% of respondents had a good level of knowledge on hypertension. The finding shows that there was a significant association between level of knowledge with educational level (p=0.001), ethnicity (p=0.001), source of health information (internet) (p=0.001) and health care worker (p=0.001) whereas the other independent variables had no statistical significance with the level of knowledge (p ˂ 0.05). Conclusion: The study concluded that less than half of respond-ents had still poor level of knowledge. Hence, mass awareness program might be helpful to increase the level of knowledge on hypertension.